Derailed Discourse in Instructional Milieu: Discourse Mode Obscurity in the Development of English Instruction Materials and Tasks for ESP - David Imamyartha (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: The use of English these days has been ubiquitous as the language is used in omnifarious contexts. That has resulted in the emergence of specific natures of English bound to context in which it is used. This specificity comprises of various aspects of communicative language ability, one of which is discourse typicality. When coupled with instructional concerns, discourse typicality has to be made obvious in every part of classroom orchestra and materials. This study took issues with scrutinizing the discourse appropriateness of tasks and materials included in ESP textbook devoted to university students. The research operationalized the framework of communicative language ability to address the research question. The research found that the textbook, in large part, had yet to involve genre, rhetorical task, interlocutor variable, and pattern of exposition specific to students’ future communicative language ability. Keywords: communicative language ability, discourse typicality, ESP.